Highly contrasted population genetic structures in a host–parasite pair in the Caribbean Sea. Issue 22 (4th October 2017) - Jossart, Quentin; De Ridder, Chantal; Lessios, Harilaos A.; Bauwens, Mathieu; Motreuil, Sébastien; Rigaud, Thierry; Wattier, Rémi A.; David, Bruno
Abstract: Evolution and population genetic structure of marine species across the Caribbean Sea are shaped by two complex factors: the geological history and the present pattern of marine currents. Characterizing and comparing the genetic structures of codistributed species, such as host–parasite associations, allow discriminating the relative importance of environmental factors and life history traits that influenced gene flow and demographic events. Using microsatellite and Cytochrome Oxidase I markers, we investigated if a host–parasite pair (the heart urchin Meoma ventricosa and its parasitic pea crab Dissodactylus primitivus ) exhibits comparable population genetic structures in the Caribbean Sea and how the observed patterns match connectivity regions from predictive models and other taxa. Highly contrasting patterns were found: the host showed genetic homogeneity across the whole studied area, whereas the parasite displayed significant differentiation at regional and local scales. The genetic diversity of the parasitic crabs (both in microsatellites and COI) was distributed in two main groups, Panama–Jamaica–St Croix on the one hand, and the South‐Eastern Caribbean on the other. At a smaller geographical scale, Panamanian and Jamaican parasite populations were genetically more similar, while more genetic differentiation was found within the Lesser Antilles. Both species showed a signature of population expansion during the Quaternary. Some results match predictive models or data from previous studies (e.g., the Western‐Eastern dichotomy in the parasite) while others do not (e.g., genetic differentiation within the Lesser Antilles). The sharp dissimilarity of genetic structure of these codistributed species outlines the importance of population expansion events and/or contrasted patterns of gene flow. This might be linked to differences in several life history traits such as fecundity (higher for the host), swimming capacity of larval stages (higher for the parasite), and habitat availability (higher for the host). Abstract : We evidenced highly contrasted population genetic structures between a host (sea urchin) and its parasite (crab) in the Caribbean Sea. This suggests the importance of distinct life history traits and larval habitat availability. This study also provides new insights into theoretical connectivity models in the Caribbean.